因式分解 求过程 x-xy+3y-3x 2x+xy-y-4x+5y-6
1个回答
x²-xy+3y-3x
=x(x-y)-3(x-y)
=(x-y)(x-3)
2x²+xy-y²-4x+5y-6
=(2x-y)(x+y)-4x+5y-6
=(2x-y+2)(x+y-3)
相关问题
因式分解:x(y-3)-(2y-6) (x+y)^3-(x-y)^2(x+y) x(x^2-xy)-(4x^2-4xy)
(x^3+y^3)^2-4xy[x^4+x^2y^2+y^4-2xy(x^2-xy+y^2)]因式分解
因式分解:12xy^2(y-x)+xy^3(x-y)+4x^2y(x-y)
若x-y=5,-xy=3,求(7x+4y+xy)-6(5/6y+x-xy)
因为3xy(2x-y)=6x^2y-3xy^2,所以因式分解6x^2y-3xy^2=
若x-y=5,-xy=3,求(7x+4x+xy)-6(5/6y+x-xy)
因式分解 3X^2+5XY-2Y^2+11X+6Y-4
因式分解1、2x^2(y+2)-3y^3(x-3)-12xy 2、x^3-4xy+4y^2-6x+12y+8
因式分解2x²+xy-y²-4x+5y-6
因式分解2x²+xy-y²-4x+5y-6